1999
DOI: 10.1097/00007890-199903270-00022
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus Disease Under New Immunosuppressive Drugs

Abstract: Recurrent rejection episodes and high dose immunosuppressive therapy, including tacrolimus, are risk factors for manifest PV kidney graft infection, which has an ominous prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(89 citation statements)
references
References 9 publications
4
82
3
Order By: Relevance
“…In this study, the distribution values of viruria/viremia was also not related to immunosuppressive therapy although the combinaison [Tac + prednisolone + MMF] was more but not statistically significant prescribed in all groups. Moreover, several studies reported that persistent BKV replication in renal allograft recipients was identified as a cause of progressive graft dysfunction and graft loss linked to immunosuppressive drugs (Tac + MMF) [3,7,10]. These findings contrast with those of this study revealed that 3 cases of acute rejections occurred in 2 patients G3 and 1 transplant recipient G4 who received this drug combina-tion.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In this study, the distribution values of viruria/viremia was also not related to immunosuppressive therapy although the combinaison [Tac + prednisolone + MMF] was more but not statistically significant prescribed in all groups. Moreover, several studies reported that persistent BKV replication in renal allograft recipients was identified as a cause of progressive graft dysfunction and graft loss linked to immunosuppressive drugs (Tac + MMF) [3,7,10]. These findings contrast with those of this study revealed that 3 cases of acute rejections occurred in 2 patients G3 and 1 transplant recipient G4 who received this drug combina-tion.…”
Section: Discussioncontrasting
confidence: 97%
“…BKV reactivation in urinary tractus, which is usually asymptomatic viruria, may occur in both immunocompetent subjects, and immunocompromised patients leading to polyomavirus associated nephropathy (PVAN) that has recently reported as a cause of allograft failure in renal transplant recipients. This nephropathy seems to be related to the conjunction of an intensive immunosuppressive regiments containing tacrolimus (Tac) or mycophenolate mofetil (MMF), an immuno-allogenic environment, a viral reactivation and a renal tubular damages caused by ischaemia or rejection [1][2][3][4]. As previously retrospective studies repported, this PVAN would be associated with loss of allograft function occurring in about half of the cases and with a major fibrosis in more than 75% of the cases in renal transplantation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…BKPyV‐associated nephropathy has been sporadically reported prior to the cyclosporine‐A (CsA) era 26, 27, but most cases have emerged after widespread clinical use of tacrolimus (TAC) and TAC‐mycophenolate 28, 29, 30, 31, 32. Data from large registries of 35 000 and more KT patients report a significantly increased risk of BKPyV for TAC‐ compared to CsA‐based regimens, while a reduced risk of BKPyV was seen for mammalian target of rapamycin (mTOR) inhibitor‐containing therapies 21, 22.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, polyomavirus‐associated nephropathy (PyVAN) occurs in 1–15% of kidney transplant recipients (KTRs), whereas polyomavirus‐associated hemorrhagic cystitis (PyVHC) affects 5–20% of allogeneic hematopoietic stem cell transplant patients 2, 9, 10. PyVAN and PyVHC have a significant impact on morbidity and graft and patient survival 11, 12, 13, 14, 15, 16, 17, 18. Despite considerable virologic research 19, 20, 21, 22, 23, randomized clinical studies either are lacking or failed to demonstrate effective antiviral therapies 24.…”
Section: Introductionmentioning
confidence: 99%